Konsep dan Desain Negara Kesejahteraan (Welfare State) - Sukmana, Oman (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2016)
AbstrakNegara kesejahteraan (welfare state) dianggap sebagai jawaban yang paling tepat atas bentuk keterlibatan negara dalam memajukan kesejahteraan rakyat. Keyakinan ini diperkuat oleh munculnya kenyataan empiris mengenai kegagalan pasar (market failure) dan kegagalan negara (state failure) dalam meningkatkan kesejahteraan rakyat. Menurut Goodin (1999; dalam Simarmata, 2008: 19) negara kesejahteraan sering diasosiasikan dengan proses distribusi sumber daya yang ada kepada publik, baik secara tunai maupun dalam bentuk tertentu (cash benefits or benefits in kind). Konsep kesejahteraan juga terkait erat dengan kebijakan sosial-ekonomi yang berupaya untuk mewujudkan kesejahteraan rakyat secara umum. Beberapa bidang yang paling mendesak untuk diperhatikan dalam kebijakan kesejahteraan adalah masalah pendidikan, kesehatan dan penyediaan lapangan kerja. Secara umum suatu negara bisa digolongkan sebagai negara kesejahteraan jika mempunyai empat pilar utamanya, yaitu: (1) social citizenship; (2) full democracy; (3) modern industrial relation systems; dan (4) rights to education and the expansion of modern mass educations systemsKata kunci : negara kesejahteraan, kegagalan pasar, kegagalan negara AbstractWelfare state is considered as the most appropriate response on the form of state involvement in advancing the welfare of the people. This belief was reinforced by the emergence of empirical facts about the failure of the market (market failure) and the failure of the state (state failure) in improving people's welfare. According to Goodin (1999; in Simarmata, 2008: 19) the welfare state is often associated with the distribution of existing resources to the public, either in cash or in the form of certain (cash benefits or benefits in kind). The concept of well-being are closely linked to socio-economic policy of working to realize the people's welfare in general. Some of the most urgent areas for attention in welfare policy is a matter of education, health and employment. In general, a country can be classified as a welfare state if it has four main pillars, namely: (1) social citizenship; (2) full democracy; (3) modern industrial relations systems; and (4) the rights to education and the expansion of modern mass Educations systems.Keywords : market failure, state failure, welfare state